2015
DOI: 10.1118/1.4935141
|View full text |Cite
|
Sign up to set email alerts
|

Vision 20/20: Mammographic breast density and its clinical applications

Abstract: Breast density is a strong predictor of the failure of mammography screening to detect breast cancer and is a strong predictor of the risk of developing breast cancer. The many imaging options that are now available for imaging dense breasts show great promise, but there is still the question of determining which women are "dense" and what imaging modality is suitable for individual women. To date, mammographic breast density has been classified according to the Breast Imaging-Reporting and Data System (BI-RAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 286 publications
0
44
0
1
Order By: Relevance
“…Given that a mammographic image is a 2-dimensional (area-based) representation of a 3-dimensional (volumetric) physiological phenomenon, numerous density assessment methods have been proposed and developed over the past 4 decades that measure various aspects of fibroglandular tissue [14,15,16,17]. These methods can be broadly classified by: (1) their mode of assessment (visual, semi-automated, fully-automated); (2) whether they measure area-based or volumetric parameters; and (3) whether they are qualitative or quantitative in nature (Figure 1).…”
Section: Mammographic Density Assessment Methodsmentioning
confidence: 99%
“…Given that a mammographic image is a 2-dimensional (area-based) representation of a 3-dimensional (volumetric) physiological phenomenon, numerous density assessment methods have been proposed and developed over the past 4 decades that measure various aspects of fibroglandular tissue [14,15,16,17]. These methods can be broadly classified by: (1) their mode of assessment (visual, semi-automated, fully-automated); (2) whether they measure area-based or volumetric parameters; and (3) whether they are qualitative or quantitative in nature (Figure 1).…”
Section: Mammographic Density Assessment Methodsmentioning
confidence: 99%
“…From this dense tissue segmentation, absolute breast tissue area and absolute dense tissue area (both in square centimeters) are derived, and PD is obtained from the ratio of dense tissue area to breast tissue area. For the purposes of this study, we focused our analysis specifically on the evaluation of PD because it is the most widely validated quantitative estimate of breast density in terms of its association with breast cancer risk (15,31). …”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, most studies on mammographic compression so far were carried out on Caucasian women [1, 3, 9, 14, 20, 24], and only one study was reported on Asian women for screen-film mammography [8]. In addition, as opposed to screen-film mammography, digital mammography has the advantage of the digital images being intensively processed to better show breast lesions and cancers compared to film images [2630], hence compression force applied in digital mammography can potentially be reduced to lower the risk of over-compression and pain in women during mammography. We want to contribute to the discussion and data on mammographic compression with this study on Asian women.…”
Section: Introductionmentioning
confidence: 99%